Relaps in orthodontic Treatment - Dr.drg. Tita Ratya Utari, Sp.Ort (Proceeding ASEAN, 2012)
A challenging problem in orthodontics is tooth relapse. the relapse of moved teeth, is an undesirable outcome of orthodontic treatment, and is a major clinical issue. the reason behind the relapse are unclear, although several factors have been suggested, including the recoil of gingival and periodontal tissues, the surrounding aoft tissues, growth of skeletal bases, and other dental factors. Transseptal fibers havu been considered to be important for stabilization of tooth position an to be source of the pressure which leads to relapse of moved teeth orthodontically